2017
DOI: 10.1111/iej.12826
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of nickel titanium rotary instrument during root canal treatment and re‐treatment: a 5‐year retrospective study

Abstract: The fracture incidence of K3 instruments was significantly greater during root canal re-treatment than root canal treatment, mainly with small instruments and in the apical third of the canals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 46 publications
(53 reference statements)
2
33
0
3
Order By: Relevance
“…The present study evaluated 487 mandibular rst molars with an RE using Schneider's method and showed that the angles of the RE root curvature in the BL and MD orientations were 40.69±14.37° and 17.58±7.84°, respectively; it was also found that most RE canals exhibited severe curvature in the BL orientation and exhibited moderate curvature or a straight appearance in the MD orientation, which is in agreement with previous studies. It is usually known that there is an increased risk of instrument fracture with an increasing angle of curvature [48][49][50]. Attention should be taken to avoid instrument fracture or perforation for the treatment of this additional unexpected canal since they are usually short and severely curved.…”
Section: Discussionmentioning
confidence: 99%
“…The present study evaluated 487 mandibular rst molars with an RE using Schneider's method and showed that the angles of the RE root curvature in the BL and MD orientations were 40.69±14.37° and 17.58±7.84°, respectively; it was also found that most RE canals exhibited severe curvature in the BL orientation and exhibited moderate curvature or a straight appearance in the MD orientation, which is in agreement with previous studies. It is usually known that there is an increased risk of instrument fracture with an increasing angle of curvature [48][49][50]. Attention should be taken to avoid instrument fracture or perforation for the treatment of this additional unexpected canal since they are usually short and severely curved.…”
Section: Discussionmentioning
confidence: 99%
“…Instrument fracture is the most common accident that occurs during the chemo-mechanical preparation when NiTi file systems are used [9][10][11]. Different thermal treatments seem to decrease its incidence [18,19], however, they are not able to eliminate it.…”
Section: Discussionmentioning
confidence: 99%
“…Different thermal treatments seem to decrease its incidence [18,19], however, they are not able to eliminate it. Cyclic fatigue, torsional resistance, and angle of distortion are important points for a better understanding of file fracture [9][10][11]. Therefore, the present study evaluated these variables comparing a new endodontic rotary file system heat-treated by new technology (CricEndo E2/F-Wire) with a traditional system heat-treated by a well-known technology (Protaper Next X2/M-Wire).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations